Considerations for biologics as front-line treatment in allergic diseases - Kothari, Akash; Hung, Lisa; Upton, Julia E. M. (Frontiers in Immunology, 2026)
The therapeutic landscape of allergic diseases has been transformed by the advent of biologics targeting key immunologic pathways. These therapies offer disease-modifying potential across a spectrum of conditions including asthma, atopic dermatitis, eosinophilic esophagitis, chronic rhinosinusitis with nasal polyps, and food allergy. However, their high cost, limited long-term safety data in some populations, and evolving eligibility criteria raise critical questions about when biologics such as monoclonal antibodies are truly warranted, especially in the context of food allergy. Agents such as omalizumab have demonstrated efficacy in raising the threshold of allergic response with monotherapy and during oral immunotherapy, improving safety profiles and accelerating desensitization. Recent developments in pharmaceutical-grade food immunotherapy and adjunctive/alternative biologic use further complicate decision-making. This expanding therapeutic toolbox necessitates a critical reassessment of when biologics are justified as front-line in allergic diseases such as food allergy. Monoclonal antibodies, in particular, are usually reserved for step-wise treatment of other diseases. It is important to have ongoing assessments as to which new and upcoming treatment modalities should be first-line. As food allergy management becomes increasingly interventional, providers must weigh the benefits of biologic therapies against real-world feasibility, health economics, and patient preference among other alternatives. Here, we discuss the current management of IgE-mediated food allergy as well as emerging therapeutics including immunotherapies and biologics. We evaluate the positioning of omalizumab in food allergy, compared with other biologics and off the shelf food-based approaches used in food allergy, and discuss clinical and research implications.